Performance comparison of WCT-03N water level control trainer system / Muhammad Amirrul Mohd Yunus - Mohd Yunus, Muhammad Amirrul (2016)
This project is focused on the comparative analysis of the two different controller applied to the WCT-03N water level control trainer system in terms of the process dynamic performances. The controllers in use for comparison are proportional and proportional plus integral control. On top of that the best tuning method is selected between Ziegler-Nichols and Cohen-Coon for both controllers, The dynamic performance is analysed in terms of percent overshoot and settling time. The result revealed that WCT-03N water level control trainer gives best performance when proportional-only controller that tuned using Ziegler-Nichols.